A Cu(II)-based coordination polymer: crystal structure and treatment activity on connective tissue disease via reducing miRNA9 expression. Issue 7 (30th April 2021) - Xue, Chenchen; Ju, Zeya; Zhang, Yongjin; Zhou, Zhiyou; Liu, Yang; Qi, Ke; He, Chongru; Bai, Xiangjun
Abstract: A new Cu(II)-containing coordination polymer formulated as [Cu(H2 L2 )(H2 O)] n (1 ) has been synthesized by the reaction of Cu(NO3 )2 ·3H2 O with a flexible 1, 1′-(propane-1, 3-diyl)bis(1H-imidazole-4, 5-dicarboxylic acid (H4 L) ligand under hydrothermal conditions. To improve the success rate of the treatment on connective tissue disease, the biological function of 1 was evaluated. First, the expression level of miRNA9 was evaluated with RT-PCR in the connective tissue disease model and normal groups. The influence of the compound on the miRNA9 expression was next explored. The differentiation ability of the tendon stem cell was further measured by evaluating the expression of the PDGF signaling pathway with western blot. Finally, the direct regulation activity of the miRNA9 on PDGF signaling pathway was confirmed with bioinformatic analysis and luciferase reporter assay. Molecular docking was performed to predict the potential binding modes of the complex to PDGF protein, indicating a possible regulation mechanism through DNA interference. Graphical Abstract: